Amniopatch procedure after previable iatrogenic rupture of the membranes: a two‐center review. (20th March 2013) - Richter, Jute; Henry, Amanda; Ryan, Greg; DeKoninck, Philip; Lewi, Liesbeth; Deprest, Jan
ABSTRACT: Objective: This study aimed to analyze success rates and pregnancy outcomes of amniopatch procedures for previable iatrogenic preterm prelabour rupture of the membranes (PPROM) with associated oligohydramnios. Methods: Retrospective analysis of amniopatch procedures performed at the University Hospitals Leuven, Belgium, and the Mount Sinai Hospital Toronto, Canada. Cases were analyzed overall and in two sub‐groups: PPROM after a needle‐based procedure (NP group, n  = 13) or after fetoscopic intervention (FI group, n  = 11). Complete technical success was defined as cessation of leakage and normalization of amniotic fluid volume, partial success as cessation of leakage, or re‐establishment of volume. Further outcomes were pregnancy duration and outcome, fetal/neonatal morbidity and mortality, and maternal morbidity. Results: Gestational age at amniopatch was comparable in both groups (NP: 20.1, FI: 21.0 weeks). Amniopatch was completely and partially successful in 29% (NP: 31%; FI: 27%) and 29% (NP: 15%; FI: 45%), respectively. Mean gestational age at delivery was 27.5 weeks (NP: 25.5; FI: 29.4 weeks). Overall neonatal survival was 17/31 (55%) (NP: 4/13 (31%), FI: 13/18 (72%); p  = .02). Chorioamnionitis occurred in three cases, two associated with maternal sepsis. Severe neonatal morbidity occurred in two survivors. Conclusion: Amniopatch for iPPROM was successful in 58%, with an overall live birth rate of 68% and survival to discharge of 55%. © 2013 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? Previable iPPROM has a poor prognosis if associated with oligohydramnios. An amniopatch procedure is technically feasible after iPPROM. What does this study add? Amniopatch procedure performed after fetoscopic iPPROM results in higher survival rates then performed after iPPROM following a needle procedure. Maternal risks are low, and no long‐term complications or deaths occurred.